Family tourism multidisciplinary perspectives - Scahanzel, Heike; Yeoman, Ian; Backer, Elisa (Buffalo : Channel View Publications, 2012)
This book brings together leading experts' latest research in the field of family tourism by adding to its underdeveloped knowledge base. It underlines the infancy of academic family tourism research that belies its market importance and directs towards future implications and theoretical debates about the place of families within tourism.
Includes bibliographical references and index.
Keywords: Tourism; Families -- Travel; Family recreation